O'Mara, John. Interview about his work in radio in Newfoundland and Labrador. - Swain, Hector K. (1990)
John O'Mara talks about his work in radio broadcasting with the CBC, and the history of early radio in Newfoundland and Labrador 00:00 - Interviewer explains his project; 01:33 - John O'Mara talks about the early days of radio in Newfoundland; Religious radio stations and programs; Religious broadcasts at Christmas; Sounds of Faith with Hiram silk; 12:58 - Sunday Miscellany with Fred Scott; Dr. A.C. Hunter; 16:13 - Talks about subscription programs. Sacred Heart program, This is My Story; 18:00 - Talks about a bass baritone singer at Harmon base in Stephenville recording Gospel and negro spirituals; Churches recording Christmas messages; 21:09 - Talks about The Invitation to Worship; Paul O'Neil, the head of the Religious Broadcasting Department and established the Religious Advisory Council. Their meetings; 27:47 - Tells a story about the generosity of a co-worker; 30:05 - Radio in Labrador; 32:14 - Talks about Reverend Lester Burry and broadcasting to Labrador; 36:07 - Gerald S. Doyle and the Doyle Bulletin from the perspective of a listener; How the Doyle Bulletin was started and is content; Phil Ryan's Bulletin in Grand Falls; Ed "Hackett" Byrne in Corner Brook; Shares some of the messages told on the Doyle Bulletin; 41:50 - Tells story about Aubrey "Mac" MacDonald reading the Bulletin; More Doyle Bulletin messages; 43:48 - Talks about a news story read by Kevin O'Connell in Corner Brook; Another story about a humorous news story from the West Coast; 46:30 - Other rolls radio played in the province; Military use; 48:48 - Talks about how most radio stations started in hotels; Talks about Cliff and Oscar Hierlihy; 51:56- VOGY started at Crosbies hotel and VONF started by the Avalon Telephone Company; Chronology of the first radio broadcasts in Newfoundland; 8JJC, 8LR, VOAS; VONF and the Newfoundland Hotel; 01:00:10 - History of the stations in Goose Bay VOUG CFGB; The station in Labrador City; Corner Brook; Other stations in the province.